PENERAPAN GUIDED INQUIRY LEARNING BERBANTUAN ADVANCE ORGANIZER MELALUI VIRTUAL EDMODO UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN KETERAMPILAN ABAD 21 (4C) SISWA SMA PADA MATERI ELASTISITAS DAN HUKUM HOOKE - Indri Eka Putri, - (2022)
Problem-solving and 21st-century skills are trained in the classroom for preparing students with the needed competencies in the digital era. The aim of this research is to describe the improvement of the student's problem solving and 21st-century skills after teaching with a guided inquiry model combined with an advanced organizer through Edmodo. The research method was mixed-method with an explanatory design. The data was collected by using essay tests of problem-solving, critical thinking, and creative thinking skills. Meanwhile, the collaboration skill used peer assessment and the communication skill used worksheets measured during the learning process. The qualitative data were gained by interviews conducted after treatment to support the findings of quantitative ones. The collected data were interpreted based on Rasch model analysis, N-Gain, and hypotheses testing. The results show that there are significant abilities of problem-solving, critical thinking, and creative thinking in the experiment class compared to the control class. The development of these skills is specified by 0.428 for problem-solving in the medium category, 0.227 for critical thinking in the low category, and 0.315 for creative thinking in the medium category. After the learning process, the achievement of collaborative and communication skills is in the very skilled, skilled, and quite skilled categories. Therefore, implementation of the learning model in the experiment class gives a positive influence toward the improvement of problem-solving and 21st-century skills (4C).